(untitled) (Scientific journal of the Fergana State University, 2025)
The presented work develops a method for calculating the solar energy flux incident on a unit area of the Earth’s surface over the course of one day. The contribution of the diffuse flux to the total flux reaching the Earth’s surface through atmospheric layers has been determined. Additionally, the calculations take into account the effect of solar radiation reflected from the Earth’s surface on the atmospheric radiation field, as well as the full spectrum of solar radiation. The calculations were carried out within the framework of Chandrasekhar’s -matrix theory. The results obtained provide recommendations for the optimal placement of heliotechnical installations on the Earth’s surface for specific geographical latitudes, which contributes to increasing their efficiency.